2020
DOI: 10.1186/s12978-020-00951-6
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Au-delà de la volonté: les conditions d’empowerment nécessaires pour abandonner les mutilations génitales féminines à Conakry (Guinée), une ethnographie focalisée

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…It also requires skill building and support to enhance individuals' economic capacities. Affirming this is Doucet et al's study in Conakry, Guinea [40] who identified that addressing the FGM/C problem involves moving beyond one's "will" to adopt essential empowerment conditions such as the provision of social support and financial independence.…”
Section: Discussionmentioning
confidence: 99%
“…It also requires skill building and support to enhance individuals' economic capacities. Affirming this is Doucet et al's study in Conakry, Guinea [40] who identified that addressing the FGM/C problem involves moving beyond one's "will" to adopt essential empowerment conditions such as the provision of social support and financial independence.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, getting pregnant before marriage is considered as a "social deviance" in the sociocultural context of Conakry. It is subject to severe family disapproval, and is even considered as a source of dishonnor for families (23), with the potential sanction of being ostracized from the familial and social solidarity networks (24). Moreover, early pregnancy or getting pregnant while studying with the risk of school dropout may result in family abandonment with a subsequent lack of nancial support, as well as in community stigma, which can have psychological, social and economic consequences (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider medicalization a harm-reduction method for FGM/C, arguing that it mitigates acute complications by as much as 70% using aseptic techniques and anaesthetics [ 11 , 13 ]. Parents have adopted the medicalization of FGM/C (done with a small incision) to protect their daughters from more invasive forms [ 14 ]. Even though their opposition to the medicalization of FGM/C, the United Nations Children's Fund (UNICEF) estimates that ¼ of the women who have undergone FGM/C worldwide, or approximately 52 million, were performed by health personnel [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This will create a social environment in which FGM/C is increasingly seen as less favourable and ultimately allow for a gradual reform of the normative and cultural-cognitive character of societies that practice FGM/C. A study conducted in Guinea showed that families who refused to have their daughters cut either had a social support network that shared the same values as them or was economically independent of the traditional solidarity network [ 14 ].…”
Section: Introductionmentioning
confidence: 99%